The teaching of African traditional religion in primary schools in Zimbabwe: challenges and opportunities - Marashe, Joel; Ndamba, Gamuchirai T.; Chireshe, Excellent (Religious Education, 2009)
Zimbabwe's Education Ministry recommended the teaching of African Traditional Religion in recognition of its multi-religious society. This study sought to establish the extent to which African Traditional Religion is taught in primary schools, the challenges faced by teachers, and opportunities for promoting its teaching. A descriptive survey design was used. A sample of 171 Bachelor of Education (In-Service) primary students of Great Zimbabwe University participated in the study. Data was collected through questionnaires and analysis of Religious and Moral Education syllabi. The study revealed that African Traditional Religion is not given due attention. Recommendations for effective teaching were made.
free
Keywords: Public schools and religion; Religion – Research; Zimbabwe – Education; Zimbabwe – Religion